INFLUENCE OF LEADERSHIP CONNECTIVITY ON PROVISION OF HOLISTIC TRAINING ON STUDENT-TEACHERS IN PUBLIC PRIMARY TEACHERS TRAINING COLLEGES - Kamamia, Lydiah Nyambura; Mugwe, Dr. Mary; Thinguri, Dr. Ruth (African Journal of Education and Practice, 2020)
Purpose: There is a great demand of well- trained teachers in the society today, and this justifies the need for an efficient, interactive training in the public primary teachers training colleges, (PTTCs), the core of education. To cater for this demand, this article reports on a study conducted on how the influence of leadership connectivity would provide holistic training on student-teachers in public primary teachers training colleges (PTTCs), in Eastern Region, Kenya. Methodology: The study used integral leadership and holistic education theories. A mixed method approach and an explanatory design collected data. Questionnaire collected quantitative data while structured interview and focus group discussion collected qualitative ones. From a population of 2061 respondents, a sample of 633 respondents comprising of 555 student-teachers, 57 lecturers who completed and returned the questionnaire, 3 principals, 3 Board of Management Chairmen who were interviewed and 15 focus group members who participated in the discussion. A mixed analysis method, involving relative frequency distribution, Chi-Square Test with p<0.05 and thematic analysis were used. The data was presented in tables showing frequencies, percentages and descriptions were summarized and interpreted. Findings: 92% of the student-teachers, 94% of the lecturers Strongly Disagreed and Disagreed that leadership in colleges encouraged interactions focused on sharing ideas and team realizations both locally and globally suggesting that leadership connectivity and holistic training were a challenge in the teacher training colleges Unique contribution to theory, practice and policy:. It was recommended that the government put in place a holistic curriculum in primary teachers training colleges for holistic training to prepare teachers with connectivity skills and knowledge.